2011
DOI: 10.4081/jphia.2011.e1
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Nigerian medical specialists on research

Abstract: The current research aimed at collating the views of medical specialists on disease priorities, class and outcomes of health research in Nigeria, and draw appropriate policy implications. Structured questionnaires were distributed to consent 90 randomly selected medical specialists practising in six Nigerian tertiary health institutions. Participants' background information, relative disease priority, research types and class, type and class of publication media, frequency of publications, challenges faced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A similar study revealed that the spectrum of research tilted more towards low-budget crosssectional surveys and retrospective studies due to the challenges of lack of funds, work overload, time constraints and insufficient infrastructural supports. 5 In the same study, 37.5% of specialists had never been in-volved in clinical trials. Incidentally, randomized clinical trials, which represent the peak of clinical evidence through the benefits of elimination of bias, form the core of evidence-based medicine.…”
Section: Introductionmentioning
confidence: 88%
“…A similar study revealed that the spectrum of research tilted more towards low-budget crosssectional surveys and retrospective studies due to the challenges of lack of funds, work overload, time constraints and insufficient infrastructural supports. 5 In the same study, 37.5% of specialists had never been in-volved in clinical trials. Incidentally, randomized clinical trials, which represent the peak of clinical evidence through the benefits of elimination of bias, form the core of evidence-based medicine.…”
Section: Introductionmentioning
confidence: 88%
“…This is obviously due to limited resources available to the researcher which then makes his main motivation for research to be the quest for promotion or the acquisition of a degree 4 . This was attested to by some Nigerian medical specialists who admitted to being involved in low budget research projects that hardly produced significant impact and outcomes 9 .…”
Section: Discussionmentioning
confidence: 99%